Protuberant fibro-osseous lesion of the temporal bone: report of four cases and review of the literature. Issue 12 (December 2021) - Bouaoud, J.; Larousserie, F.; Galmiche-Rolland, L.; Bouvier, C.; Picard, A.; Khonsari, R.H.
Abstract: 'Bullough lesions', also referred to as protuberant fibro-osseous lesions (PFOL), are rare temporal bone lesions initially described in 1999. Since only 12 cases have been reported, several key issues, such as their origin and recommended management strategies, remain unresolved. This article reports the largest cohort included in the literature to date, comprising four patients with PFOL. PFOL appears to be characterized by female and right-side predominance. These lesions were consistently located regarding the mastoid, generally diagnosed in early adulthood, without functional symptoms, and were always fibro-osseous. Invasive/malignant features were not found on imaging or histology. The main differential diagnosis was malignant low-grade parosteal osteosarcoma. Clinical examination and computed tomography images provided strong elements supporting the diagnosis of PFOL. Biopsy allowed molecular biology investigations ( MDM2 and CDK4 amplification), in order to rule out low-grade parosteal osteosarcoma.